2000
DOI: 10.1007/s004250050691
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of LeAGP-1, a modular arabinogalactan-protein, reveals its developmentally regulated expression in tomato

Abstract: Arabinogalactan-proteins (AGPs) are highly glycosylated cell surface proteins that are thought to function in plant growth and development. The developmentally regulated expression of LeAGP-1, a novel and major AGP in tomato, was examined in different organs and tissues of tomato (Lycopersicon esculentum Mill. cv. UC82B) plants with an anti-peptide antibody (i.e. the PAP antibody) directed specifically against the lysine-rich subdomain of the LeAGP-1 core protein. During cell differentiation in tomato plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
2
43
0
2
Order By: Relevance
“…In most cases, the proteins were localized in epidermal cells [(SPPPP) 15 ]. The tissue expression of LeAGP1 in Arabidopsis stems is similar to that described for tomato stems (Gao et al, 1999;Gao and Showalter, 2000), although the epidermal cells were not reactive in the latter with the polyclonal PAP antibody (reacts against the Lys-rich subdomain of the Le-AGP1 protein backbone).…”
Section: Expression Of Syngms In Adult Plantssupporting
confidence: 74%
See 2 more Smart Citations
“…In most cases, the proteins were localized in epidermal cells [(SPPPP) 15 ]. The tissue expression of LeAGP1 in Arabidopsis stems is similar to that described for tomato stems (Gao et al, 1999;Gao and Showalter, 2000), although the epidermal cells were not reactive in the latter with the polyclonal PAP antibody (reacts against the Lys-rich subdomain of the Le-AGP1 protein backbone).…”
Section: Expression Of Syngms In Adult Plantssupporting
confidence: 74%
“…3A and 4, B and C). Similar tissue expression was found in tomato plants (Gao and Showalter, 2000). LeAGP1 orthologs in Arabidopsis (AtAGP17, AtAGP18, and AtAGP19) are Incubation of a leaf extract at room temperature (RT) with or without urea, before electrophoresis produced a band of expected molecular mass of the nonglycosylated construct (white arrowhead) together with other bands of higher M r , but no band is detected at 27 kD (*).…”
Section: Expression Of Syngms In Arabidopsismentioning
confidence: 52%
See 1 more Smart Citation
“…For example, in tomato, LeAGP-1 messenger RNA (mRNA) is found in young but not old stems and fruit [12,13]. Interestingly, the LeAGP-1 glycoprotein is detected at both temporal stages, providing some support to the notion that AGPs are stable molecules once produced and may accumulate over time [75]. At the tissue (and cellular) level, immunolocalization studies have revealed developmental patterns of AGP expression.…”
Section: Agp Expression In Plant Organs and Tissuesmentioning
confidence: 99%
“…(see table 2). More specifically, such AGPs are associated with, and hypothesized to function in, secondary cell wall thickening and programmed cell death (PCD) [39,75]. Here, AGPs which are located at the cell surface of differentiating xylem elements may serve to position or interact with wall components, including themselves, and thus contribute to wall thickening.…”
Section: Vegetative Growth and Developmentmentioning
confidence: 99%